Pengaruh Permainan Tradisional Gobak Sodor Terhadap Peningkatan Kelincahan Siswa Sekolah Dasar - Bawazir, Ibnu Alif; Fauzi, Rizal Ahmad; Rukmana, Anin (Universitas Hamzanwadi, 2024)
The problem is the lack of playing agility in students when participating in traditional game learning. The purpose of this study was to improve student agility through traditional games of gobak sodor. The method in this study is an experimental method with a one group pretest posttest design. The population in this study were grade VI students of SDN 6 Arjawinangun with a total of 24 people. the sampling technique was total sampling. So the number of samples in this study were 24 people. The instrument in this study used a back and forth running test. The data collected is the average of the pre-test and post-test results. The data were then tested using the normality test, homogeneity, paired sample t-test and R-Square test in SPSS 20 statistics. The results showed R Square of 0.675 found 67.5%. Paired Sample T-test (0.001) < (0.05). homogeneity test (0.790) > α (0.05). normality test of 0.072. it is concluded that there is an effect of traditional gobak sodor games on increasing the agility of elementary school students and in the GOOD percentage category.